Carbon Nanotubes Enabling Highly Efficient Cell Apoptosis by Low‐Intensity Nanosecond Electric Pulses via Perturbing Calcium Handling. Issue 1 (4th December 2019) - Mao, Zheng; Zhang, Youyu; Lu, Nan; Cheng, Shun; Hong, Ronghan; Liu, Qing Huo
Abstract: Effective induction of targeted cancer cells apoptosis with minimum side effects has always been the primary objective for anti‐tumor therapy. In this study, carbon nanotubes (CNTs) are employed for their unique ability to target tumors and amplify the localized electric field due to the high aspect ratio. Highly efficient and cancer cell specific apoptosis is finally achieved by combining carbon nanotubes with low intensity nanosecond electric pulses (nsEPs). The underlying mechanism may be as follows: the electric field produced by nsEPs is amplified by CNTs, causing an enhanced plasma membrane permeabilization and Ca 2+ influx, simultaneously triggering Ca 2+ release from intracellular storages to cytoplasm in a direct/indirect manner. All the changes above lead to excessive mitochondrial Ca 2+ uptake. Substructural damage and obvious mitochondria membrane potential depolarization are caused subsequently with the combined action of numerously reactive oxygen species production, ultimately initiating the apoptotic process through the translocation of cytochrome c to the cytoplasm and activating apoptotic markers including caspase‐9 and ‐3. Thus, the combination of nanosecond electric field with carbon nanotubes can actually promote HCT116 cell death via mitochondrial signaling pathway‐mediated cell apoptosis. These results may provide a new and highly efficient strategy for cancer therapy. Abstract : A physical method that combines carbon nanotubes with low intensity nanosecond electric pulses (nsEPs) is proposed for highly efficient cancer cell apoptosis induction. Mechanism research suggests that carbon nanotubes are able to amplify the electric field, enhancing the membrane permeabilization and intracellular effects induced by nsEPs, ultimately triggering mitochondrial signaling pathway‐mediated cell apoptosis by perturbing calcium handling.